A inserção dos tablets em escolas estaduais de Aracaju : desafios e limitações - Pinto, Maiara Fernanda Souza (2016)
Mobile technologies, especially tablets, are bringing a new concept of teaching called mobile learning which is related to spatial mobility and time at school. In Sergipe, in 2013, it implemented the Educational Tablets project aiming to provide teachers and students conditions of access to new technologies and the Internet to assist student learning. This research aimed to investigate the chemistry teachers so accept the inclusion of tablets in their teaching in schools of Aracaju State network. For this, they were carried interviews with two officials from the SEED / SE, better understand the project and later with seven chemistry teachers of schools where teachers and students received the tablet. The sample was analyzed from the "Textual Analysis Discourse - ATD". The analysis of these data and the comments "free" after the interviews conclude that chemistry teachers accept the inclusion of tablets, but in this SEED / SE project, there was no incorporation of the same in their teaching practices. In our emerging understanding, it is not enough to equip the school with technological resources without developing the teacher stimulation, training a good continuing education and its role in the project from its conception, so they do not feel compelled to simply use them.